Participation in a prostate cancer support group and health literacy. Issue 10 (14th September 2018) - Haack, Marius; Kofahl, Christopher; Kramer, Silke; Seidel, Gabriele; von dem Knesebeck, Olaf; Dierks, Marie‐Luise
Abstract: Background: To cope with prostate cancer (PC) and its consequences and to be certain about therapeutic alternatives, some patients seek mutual help in prostate cancer support groups (PCSGs), where they share information and find social support. Our study was intended to assess whether group participation is associated with health literacy (HL). Methods: We compared PCSG members (n = 441) with PC patients without support group experiences (n = 135) in a cross‐sectional design. For this purpose, HL was operationalized through PC‐specific knowledge, noncancer‐specific knowledge about health care, guideline awareness, and skills needed to apply health information to meet own needs. Binary logistic regression models were calculated. Socio‐demographic data and disease‐related characteristics were used as control variables. Results: Knowledge about PC (OR, 2.2; CI, 1.3‐3.7), the fact of having heard of guidelines (OR, 3.7; CI, 2.1‐6.8) and having read one (OR, 5.1; CI, 2.8‐9.4), and competencies regarding health service navigation (OR, 1.8; CI, 1.0‐3.1) are associated with PCSG membership. No statistically significant associations could be found between PCSG membership and further skills questioned, as well as between membership and knowledge about noncancer‐specific health care. Conclusion: PCSG membership is associated with HL in some areas only. In particular, the groups seem to provide an important platform for information exchange in the field of PC. The potentially conflicting results on PC knowledge and the application skills may arise from the different forms of measurement—knowledge was tested; skills were self‐assessed.